2004
DOI: 10.1016/j.jacc.2004.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Anemia as a risk factor and therapeutic target in heart failure

Abstract: Anemia has recently been recognized as an important comorbid condition and potentially novel therapeutic target in patients with heart failure (HF). Anemia is common in HF patients, with a prevalence ranging from 4% to 55% depending on the population studied. Multiple potential mechanisms of interaction exist between anemia and the clinical syndrome of HF, including hemodilution, inflammatory activation, renal insufficiency, and malnutrition. A growing body of literature from observational databases and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
4
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(165 citation statements)
references
References 71 publications
7
142
4
11
Order By: Relevance
“…This study shows, in accordance with several previous reports, that anemia is frequent in chronic HF patients and associated with a lower exercise capacity [1][2][3][4][5][6]. Indeed, the prevalence of anemia we observed (26%) is in agreement with what has been reported previously (between 10 and 55%) [4].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study shows, in accordance with several previous reports, that anemia is frequent in chronic HF patients and associated with a lower exercise capacity [1][2][3][4][5][6]. Indeed, the prevalence of anemia we observed (26%) is in agreement with what has been reported previously (between 10 and 55%) [4].…”
Section: Discussionsupporting
confidence: 93%
“…Anemia and reduction of exercise capacity are both frequently reported in chronic heart failure (HF) and are both associated to worsening of HF prognosis [1][2][3][4]. The two are linked to each other indirectly, having heart failure as a common underlying origin, and directly.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that RDW may be related to the degree of infl ammation, inadequate production of erythropoietin, renal function, and nutritional status. [16][17][18] In the present study, patients with a 90-day adverse event had lower BMI, albumin, total cholesterol, triglycerides, and low-density lipoprotein cholesterol, fi ndings that are consistent with those of a previous study. 6) RDW might have clinical relevance as an easy and inexpensive surrogate marker for nutritional status associated with a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our finding, several studies have also shown that low hemoglobin levels were strongly associated with higher risk of mortality in HD patients (25,26). Evidence shows that maintaining the hemoglobin level of HD patients at the normal range, is associated with increase in quality of life (27), improvement of cardiac and brain function (28,29) and decrease in hospitalization and cost of treatment (30). Our study confirmed the previous findings that, low serum albumin is related with severe survival (14,31,32).…”
Section: Discussionsupporting
confidence: 89%